Two news species of Corallistidae (Porifera; Demospongiae; Tetractinellida) with a first record of Awhiowhio from the Atlantic - Dias, Alan; Kelly, Michelle; Pinheiro, Ulisses (Zootaxa, 2023)
In the present study, we describe two new species of Corallistidae from Brazil, comparing them to all valid species of the respective genera. Both are notable Porifera records, with the first specimen of Neophrissospongia Pisera and Lévi, 2002 registered for the Brazilian coast and the first specimen of Awhiowhio Kelly, 2007 registered for the Atlantic Ocean. The specimens were preserved in 80% ethanol and analyzed following classical procedure for Demospongiae, with dissociated spicule mounts, skeletal sections and Scanning Electron Microscopy. Neophrissospongia jorgeorum sp. nov. is differentiated from its congeners by the categories of spicules present, especially the lack of streptasters/amphiasters. Awhiowhio saci sp. nov. is characterized especially by the presence of spiraster-shaped microrhabds and microxeas.